Effects of peptide fraction and counter ion on the development of clinical signs in experimental autoimmune encephalomyelitis. (13th February 2014) - Boullerne, Anne I.; Polak, Paul E.; Braun, David; Sharp, Anthony; Pelligrino, Dale; Feinstein, Douglas L.
Abstract The most commonly used immunogen to induce experimental autoimmune encephalomyelitis is MOG35‐55, a 21‐residue peptide derived from myelin oligodendrocyte glycoprotein (MOG). In most studies, mice exhibit a chronic disease; however, in some studies mice show a transient disease. One variable that is not often controlled for is the peptide fraction of the purified MOG material, which can vary from less than 50% to over 90%, with the remainder of mass primarily comprised of the counter ion used for peptide purification. We compared the development of clinical signs in female C57Bl6 mice immunized with two commercially available MOG35‐55 peptides of similar purity but different peptide fraction (MOG‐A being 45%; MOG‐B being 72%). A single immunization with MOG‐A induced a chronic disease course with some recovery at later stages, whereas immunization with MOG‐B induced a similar course of disease but with significantly lower average clinical scores despite a higher peptide content. The addition of a booster immunization significantly increased clinical severity with both preparations, and significantly reduced the average day of onset using MOG‐A. To determine if the counter ion could influence disease, we compared MOG‐B‐containing trifluoroacetate with MOG‐B‐containing acetate. Although disease incidence and severity were similar, the average day of disease onset occurred approximately 5 days earlier with the use of MOG‐B‐containing trifluoroacetate. These results demonstrate that differences in peptide fraction influence the course of encephalomyelitis disease, which may be due in part to the levels of counter ions present in the purified material. These findings underscore the fact that a knowledge of peptide fraction is as critical as knowledge of peptide purity when using peptides from different sources. <boxed-text content-type="graphic" id="jnc12664-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> The most commonly used immunogen to induce experimental autoimmune encephalomyelitis (EAE) is MOG35‐55, a 21‐residue peptide derived from myelin oligodendrocyte glycoprotein. Subtle variations in MOG immunization protocols can influence the type of disease, the average day of onset, disease severity, and overall incidence. We hypothesized that variance in peptide fraction and counter ion may contribute to those differences. Surprisingly, immunization with a MOG preparation of high (72%) peptide fraction resulted in lower average EAE clinical scores and later disease onset than immunization with a preparation having only 45% peptide fraction. Replacement of trifluoroacetate (TFA), the counter ion used for MOG peptide purification, with acetate delayed disease onset. These results show that knowledge of peptide fraction and the counter ion present are as critical as peptide purity, particularly when using peptides from different sources. The image shows TFA molecules (not to scale) hypothetically binding to the positively charged residues of MOG.